group guidance, image media, spe Group guidance using the storytelling method using series of picture media to improve the speaking skills of children aged 5-6 years at RA Nawira Aulia: Counseling Guidance Action Research - hanifah, alfina (Jurnal Psikoedukasia, 2025)
Alfina Hanifah “Group guidance using the storytelling method using series of picture media to improve the speaking skills of children aged 5-6 years at RA Nawira Aulia." Thesis. Guidance and Counseling Study Program, Faculty of Education, PGRI University Semarang. Supervisor I Eka Sari Setianingsih, S.Pd., M.Pd. Supervisor II Agus Setiawan. S.Pd., M.Pd. This study aims to improve the speaking skills of children aged 5-6 years at RA Nawira Aulia through group counseling using storytelling with a series of picture media. This research employs a Counseling Guidance Action Research (PTBK) design consisting of two cycles, each with two sessions, involving 8 children. Data were collected through observation and documentation. The results show a significant improvement in children's speaking abilities. In the pre-cycle, 87% of children were categorized as sufficient, and in the second cycle, 87% of children reached the very good category. This study suggests the use of picture series media to support children's speaking development in learning activities.